Increasing effectiveness of conditional cash transfer for eradicating child labor - HWANG, Miae (KDI School, 2015)
The study aimed to analyze whether subsidies from the Indonesian conditional cash transfer program were successful in reducing the participation of children in the labor force. One of the expected effects of conditional cash transfers is reducing child labor by making children affordable to spend more time in school instead of the work place. However, the Indonesian conditional cash transfer program, Program Keluarga Harapan, did not improve child labor significantly. To figure out the reasons for this failure, this study conducted a financial analysis of children who are participating in the program by using the Indonesia Family Life Survey data from the RAND Corporation and Indonesian statistical data. The results demonstrated that the amount of subsidy was too low to make children go to school, driving children to choose to work instead of studying; hence, reducing educational expenditure or increasing subsidies by incorporating scholarship is required. Furthermore, when the study compared program beneficiaries and non-beneficiaries with future scenarios, the results showed that not participating in the program would be better for children who already have dropped out of the school. On the other hand, it illustrated that acquiring a diploma is important once they start studying in school.
Thesis(Master) --KDI School:Master of Development Policy,2015